Kirjanpitotilojen tuotanto- ja investointisuunnitelmat Suomessa - Rantamäki-Lahtinen, Leena; Remes, Katariina; Koikkalainen, Kauko (MTT, 2002)
The aim of this stydy was to examine what kind of agricultural production and investment plans bookkeeping farmers had in 2001. The data was collected by postal survey in 2001. The survey was sent to all Finnish bookkeeping farms, excluding greenhouse enterprises. The survey was sent to 1 056 farms. The response rate was 74%. The collected survey data was integrated with the bookkeeping results. Most farmers (87% of the respondents) intents to continue farming by themselves during 2001-2005. Approximately 9% of farmers were planning succession in their farm during the same period. These two groups had different plans for future production, especially those concerning the animal production. On those farms, where farmers intented to continue farming themselves, 68% of the farmers planned to maintain the current level of animal husbandry and 21% to expand it. On the other hand, on those farms, which were preparing to succession 45% intended to maintain the current level, 27% to expand it and 22% to give up the animal husbandry. Farms that intended to expand their agricultural production were bigger than those farms that intended to maintain the current level of production. The average turnover and operating profit were bigger in expanding farms. On the other hand, their depreciation, financing costs and liabilities were higher. Thus, those farms, which were going to expand had already earlier invested more into agriculture. Quite naturally, expanding farms were going to invest more to agriculture than the others did. 55% of the farms were pluriactive. 25% of the farms had diversified their activities to nonagricultural on-farm or off-farm entrepreneurship. In addition, in 44% of the farms had least some income from off-farm employment. Pluriactivity is more common in crop producing farms than in livestock farms. The on-farm and off-farm diversification is common in all farm sizes. On the contrary, the off-farm employment was more common in small farms than in big farms. 80% of those farms, which were smaller than 8 ESU had income from off-farm employment.
OB Kirjanpitotilojen tuotantoa ja toimeentuloa koskevat suunnitelmat vuoteen 2005
Keywords: Ma; Suomi; maatalous; investoinnit; tuotanto; agriculture; Finland; investments; production